(untitled) (Thành phố Hồ Chí Minh, 1997)
The themes are integrated across proficiency levels and the levels are articulated across skill strands. The series combines communicative activities with skill-building exercises to boost students' academic success
Keywords: Tiếng Anh,English language; Sách giáo khoa cho người nước ngoài,Textbooks for foreign speakers